Kearifan Lokal Buton Dalam Pendidikan Anak (Falsafah Binci-binciki Kuli dan Aplikasinya pada Anak di Kota Baubau) - Fasilia Fasilia (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2013)
This study aims to determine how the process of planting the values and philosophy BBK determinant factors that influence it. This research is a qualitative descriptive using observation, interviews and documentation. The study concluding that the process of planting philosophy values BBK (pengobjektivasian process value) to the child's parents can do informally within the family environment, and teachers in the formal school environment in the learning process by providing examples of good behavior.